The Effect of FDR, ROE, ROA, and NPF on Profitability in Indonesian Sharia Commercial Banks - Akbar Al Almer; Nur Hidayah (IECON: International Economics and Business Conference, 2023)
This study aims to analyze the effect of the Financing to Deposit Ratio (FDR),Return on Equity (ROE), Return on Asset (ROA), and Non-Performing Financing (NPF)on Profitability in Indonesia with 8 Sharia Banks in Indonesia from 2016 - 2021. This study used the panel data method using the software eviews 10. From the results of the study, it shows that the Fixed Effect Model (FEM) is the most appropriate. The regressionof this study shows that the variable Return on Equity, Financing to Deposit Ratio has a positive and significant effect on Profitability. The variable Return on Asset has a Negative and Significant effect on profitability. Meanwhile, the Variable Non PerformingTo Deposit Ratio has a negative and insignificant effect. Based on the simultaneous test of Financing to Deposit Ratio, Return On Equity, Return On Asset and Non Performing Financing was significant at 98.62% and the remaining 1.38% was influenced by other factors that were not included in the model. This research is expected to the Indonesian government to pay attention to the influence of FDR, ROE, ROA, and NPF on profitability in each Bank Region of Indonesia.